Factors related to quality of life among stroke survivors - Chuejedton, Rangsiya; Tamdee, Decha (Journal of Associated Medical Sciences, 2017)
Background: Stroke is a major health problem effected to stroke patients, especially to quality of life among stoke survivors. Objectives: To explore quality of life (QOL) and factors related to quality of life in 140 stroke survivors at Chiang Dao city of Chiang Mai Province. Materials and methods: This study is a descriptive correlational research of stroke survivors to Amphur Chiang Dao, Chiang Mai Province. Subjects were questioned about demographics data, severity of disease, level of activity daily living and quality of life. The instruments used for data collection was questionnaire for demographic data, Modified Rankin Scale, Barthel ADL Index and Quality of Life Questionnaire developed by Ferrans and Powers. Data analysis was performed using descriptive statistics, point biserial correlation, Spearman rank correlation coefficient and multiple regression analysis. Results: The results revealed that mean scores of overall QOL of life, health and functional ability, psychological/ spiritual, social and economic and family dimensions of participants were at a moderate level. Factors including personel relationship with people in community, care giver environments and muscle power of upper extremity were shown significantly correlated with the quality of life in stroke survivors as same as the level of severity and level of activity daily living (p<0.05). In addition, independent factors include co-morbidity, drinking alcohol, care giver, duration of caring, duration of stroke and level of severity were significantly influencing the predictors of quality of life of stroke survivors (p<0.05). Conclusion: The findings can be used as a guide to develop rehabilitation programs to improve overall quality of life.